Tracheal intubation with the Bonfils fiberscope in the difficult pediatric airway: a comparison with fiberoptic intubation. Issue 4 (12th September 2014) - Kaufmann, Jost; Laschat, Michael; Engelhardt, Thomas; Hellmich, Martin; Wappler, Frank; Cote, Charles
Summary Background Fiberoptic intubation (FOI) is the gold standard for the tracheal intubation in adults with a difficult airway. However, this technique is more difficult in the narrow pediatric airway and the evaluation of alternative devices in children remains desirable. The Bonfils fiberscope (BF) is well described for the difficult airway, but no clinical data assessing its use in the difficult pediatric airway are available. Methods A controlled clinical study was conducted comparing BF and FOI in children and infants requiring tracheal intubation with a suspected difficult airway or who demonstrated a difficult airway which was unanticipated. Time to successful intubation, quality of imaging and ease of the intubation procedure were determined. Results A total of 26 patients (46% infants) were studied, and all successfully intubated at the first attempt using either the BF or FOI. Mouth opening was restricted in 38% of patients. Time required for intubation was shorter with the BF (52 ± 22 s) compared with the FOI (83 ± 24 s, P = 0.008). The image quality (excellent in 73% vs 45%, P = 0.129) and the ease of the procedure (excellent in 67% vs18%, P = 0.015) were considered better with BF than with FOI. Conclusion Although both the BF and FOI are suitable devices for the intubation of infants and children with difficult airways, the BF may allow faster tracheal intubation with a better image quality and ease of use.